Assessing Customer Satisfaction in Islamic Rural Banks: An Importance-Performance Analysis of BPRS Amanah Bangsa - Yayat Rahmat Hidayat; Popon Srisusilawati; Nanik Eprianti; M. Andri Ibrahim (Journal of Islamic Economics and Business, 2025)
This study measures customer satisfaction at BPRS Amanah Bangsa using Importance-Performance Analysis (IPA). While previous research has mainly examined Islamic commercial banks, this study extends the application of IPA to Islamic rural banks, offering micro-level insights into service quality attributes often overlooked in the literature. Results show an average conformity level of 106.47% and a Customer Satisfaction Index (CSI) of 66.24%, indicating customers are generally satisfied. However, gaps remain in promotional tools, service responsiveness, and customer data privacy. The findings contribute by highlighting critical service areas for improvement in BPRS and demonstrating the applicability of IPA in strengthening the competitiveness of small-scale Islamic financial institutions.